2015
DOI: 10.1093/rheumatology/keu528
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory role of IL-35 in T cells of patients with rheumatoid arthritis

Abstract: These data revealed that IL-35 might suppress T cell activation during the peripheral immune responses of RA. Therefore our data suggest that IL-35 might have multiple therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 22 publications
6
38
0
1
Order By: Relevance
“…42 While excess T H 1 cell and T H 17 cell activity can contribute to RA pathology, reduced frequencies of tolero genic regulatory T (T REG ) cells are also a feature of autoimmune disease that could similarly contribute to the pathology of RA. Consistent with this hypothesis, levels of anti-inflammatory cytokines such as IL-10, transforming growth factor β 43 and the novel IL-12-family cytokine IL-35 44,45 are reduced in serum from patients with RA. However, findings have been contradictory regarding the frequency of peripheral T REG cells in patients with RA relative to healthy controls, 46 and no difference in T REG cell frequency has been observed between patients with RA or osteoarthritis.…”
Section: Reviewsmentioning
confidence: 65%
“…42 While excess T H 1 cell and T H 17 cell activity can contribute to RA pathology, reduced frequencies of tolero genic regulatory T (T REG ) cells are also a feature of autoimmune disease that could similarly contribute to the pathology of RA. Consistent with this hypothesis, levels of anti-inflammatory cytokines such as IL-10, transforming growth factor β 43 and the novel IL-12-family cytokine IL-35 44,45 are reduced in serum from patients with RA. However, findings have been contradictory regarding the frequency of peripheral T REG cells in patients with RA relative to healthy controls, 46 and no difference in T REG cell frequency has been observed between patients with RA or osteoarthritis.…”
Section: Reviewsmentioning
confidence: 65%
“…Human IL-35 expression has been reported in chronic hepatitis B virus-infected patients [31], normal pregnancies [32], sepsis [33], and rheumatoid arthritis [34]. In support of a mathematical modeling analysis that reported a correlation between IL-35 and tumors [16], we demonstrate that elevated IL-35 level in CRC patients is coincident with an increase in Treg cells and it was mainly expressed in CD4 + T cells in human colorectal cancer and adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study has indicated that IL-35-producing B cells play an important role in the regulation of immunity, and a potential therapeutic value for IL-35 production by B cells in autoimmune and infectious diseases has been proposed (Shen et al 2014). In another study, Nakano et al (2015) focused on the regulatory role of IL-35 in T cells of patients with RA. They observed that IL-35 exhibited an immunosuppressive role in T cell activation during the immune response elicited in RA.…”
Section: Discussionmentioning
confidence: 99%